Teacher Educators’ Attitudes towards Personalized Learning: A Comparative Study - Wajeeha Shahid (JCTE, 2023)
This study was designed to assess and compare teacher educators’ attitude towards personalized learning at higher level in Pakistan. It was a descriptive study done in the Pakistani context. Sample included teacher educators serving in two public and two private sector universities situated in Islamabad. Results obtained from a 26 item 5 point Likert scale questionnaire revealed that teacher educators of both the sectors were using five aspects of personalized learning namely access to technology, student involvement, teacher as a facilitator, two way collaboration and manageable class size as per Basye Model.